Excess stock returns and corporate environmental performance in China - Dandan Ma; Pengxiang Zhai; Dayong Zhang; Qiang Ji (Financial Innovation, 2024)
Abstract Using unbalanced panel data on 3326 Chinese listed companies from 2014 to 2021, this study investigates the impact of corporate environmental performance on China’s excess stock returns. The results show that stocks of companies with better environmental performance earn significantly higher excess returns, indicating the existence of green returns in the Chinese stock market. We further reveal that heightened climate-change concerns can boost the stock market’s green returns, while tightened climate policies decrease green returns by increasing long-term carbon risk. Our findings are robust to endogeneity problems and hold great implications for both investors and policymakers.